Can diagnosis-based capital allocation facilitate more appropriate, sustainable and innovative acute care? - Kerr, Rhonda Ann (Curtin University, 2019)
Australians value access to public hospitals with technologically-appropriate clinical care. However, the Australian system of capital funding for public hospitals is not appropriate, effective, equitable, clinically-responsive, patient-centred, evidence-based or sustainable. A new model to effectively fund patient access to efficient public hospitals was developed from international evidence, Australian standards, clinical guidelines and expert clinical interviews. Capital was costed by patient diagnosis group to enable comprehensive funding for public hospital clinical care, for the first time.